ANALISIS YURIDIS TINDAK PIDANA PERDAGANGAN ORANG (STUDI PUTUSAN NOMOR: 1897/PID.SUS/2022/PN.MDN) - Manurung, Rauf Sharim; Zulfan, Zulfan; Nasir, Muhammad (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
Abstract          This research aims to find out the form of legal protection for child victims of sexual exploitation, and to find out the decision Number 1897/Pid.Sus/2022/ PN.Mdn is in accordance with the application of Law No. 21 of 2007 concerning Eradication of Trafficking in Persons. The type of research used is Normative juridical with a legislative research approach and sources of legal materials, namely primary, secondary and tertiary legal materials. The results showed that the form of legal protection for child victims of sexual exploitation is currently far from expectations, seeing the obstacles that still need serious attention from all parties involved in efforts to deal with sexual exploitation of children. Decision Number 1897/Pid.Sus/2022/ PN.Mdn should be better if the defendant is subject to Article 82 paragraph (1), Article 76E. The judge decided that the facts revealed in the trial were a juridical matter, in Decision Number: 1897/Pid.Sus/2022/Pn.Mdn the judge did not provide restitution rights for child victims, whereas according to Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons article 48 paragraph (1) every victim of the crime of trafficking in persons or their heirs is entitled to restitution, as well as healing for child victims in immaterial matters in the form of health and psychological child victims. keyword: Child Exploitation, Restitution, Human Trafficking.